A severe clinical phenotype of Noonan syndrome with neonatal hypertrophic cardiomyopathy in the second case worldwide with RAF1 S259Y neomutation. (2019) - Jaouadi, Hager; Chehida, Amel Ben; Kraoua, Lilia; Etchevers, Heather C.; Argiro, Laurent; Kasdallah, Nadia; Blibech, Sonia; Delague, Valérie; Lévy, Nicolas; Tebib, Néji; Mrad, Ridha; Abdelhak, Sonia; et al.
Abstract: Noonan syndrome and related disorders are a group of clinically and genetically heterogeneous conditions caused by mutations in genes of the RAS/MAPK pathway. Noonan syndrome causes multiple congenital anomalies, which are frequently accompanied by hypertrophic cardiomyopathy (HCM). We report here a Tunisian patient with a severe phenotype of Noonan syndrome including neonatal HCM, facial dysmorphism, severe failure to thrive, cutaneous abnormalities, pectus excavatum and severe stunted growth, who died in her eighth month of life. Using whole exome sequencing, we identified a de novo mutation in exon 7 of the RAF1 gene: c.776C > A (p.Ser259Tyr). This mutation affects a highly conserved serine residue, a main mediator of Raf-1 inhibition via phosphorylation. To our knowledge the c.776C > A mutation has been previously reported in only one case with prenatally diagnosed Noonan syndrome. Our study further supports the striking correlation of RAF1 mutations with HCM and highlights the clinical severity of Noonan syndrome associated with a RAF1 p.Ser259Tyr mutation.